Development of a New Inhibition Kinetic Spectrophotometric Method for Determination of Resorcinol Based on its Inhibitory Effect on Formaldehyde Catalyzed Reaction Between Bromate and Janus Green - KEYVANFARD, MOHSEN (Asian Journal of Chemistry, 2010)
A new, simple, sensitive and fast kinetic spectrophotometric method was developed for the determination of trace amounts of resorcinol over the range of 0.02-0.60 μg/mL. The method is based on the inhibitory effect of resorcinol on the formaldehyde catalyzed oxidation reaction of Janus Green by bromate in acidic media is reported. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of Janus Green at 554 nm with a fixed-time 0.5-2.0 min from initiation of the reaction. The detection limit is 0.012 μg/mL and relative standard deviation of 0.04 and 0.08 μg/mL resorcinol for six replicate measurements was 2.5 and 2.9 %, respectively. The method was applied to the determination of resorcinol in water samples.